2021
DOI: 10.1093/ofid/ofab567
|View full text |Cite
|
Sign up to set email alerts
|

Triage of Persons With Tuberculosis Symptoms Using Artificial Intelligence–Based Chest Radiograph Interpretation: A Cost-Effectiveness Analysis

Abstract: Background In settings without access to rapid expert radiographic interpretation, artificial intelligence (AI)–based chest radiograph (CXR) analysis can triage persons presenting with possible tuberculosis (TB) symptoms, to identify those who require additional microbiological testing. However, there is limited evidence of the cost-effectiveness of this technology as a triage tool. Methods A decision analysis model was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For the first full economic evaluation, researchers developed a decision-analysis model to assess the cost-effectiveness of CAD as a triage tool for patients presenting with TB symptoms in a low-income, high TB incidence population in Pakistan. 24 Compared to the status quo of smear microscopy and GeneXpert, with no prior triage, CAD as a triage tool was projected to reduce costs by respectively 19% and 37% while averting 3–4% additional disability-adjusted life-years. An active case-finding intervention using mobile CXR units equipped with CAD and Xpert testing was found to be cost-effective in Zambia, especially in populations with high HIV and TB mortality.…”
Section: Economic Aspectsmentioning
confidence: 99%
“…For the first full economic evaluation, researchers developed a decision-analysis model to assess the cost-effectiveness of CAD as a triage tool for patients presenting with TB symptoms in a low-income, high TB incidence population in Pakistan. 24 Compared to the status quo of smear microscopy and GeneXpert, with no prior triage, CAD as a triage tool was projected to reduce costs by respectively 19% and 37% while averting 3–4% additional disability-adjusted life-years. An active case-finding intervention using mobile CXR units equipped with CAD and Xpert testing was found to be cost-effective in Zambia, especially in populations with high HIV and TB mortality.…”
Section: Economic Aspectsmentioning
confidence: 99%
“…Cost and resource demand are high, especially during large-scale prevalence surveys, and performing microbiological testing on all participants is often infeasible. Therefore, tools such as digital chest radiography and CAD offer a potential solution by being an accurate screening/triage test, while also being cost-effective [ 37 , 38 ]. However, a proportion of participants who do not undergo microbiological diagnostic testing, for example, those who are asymptomatic or had a normal-appearing chest x-ray, may in fact have TB and be potentially missed.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, some studies have shown the effectiveness of chest X-ray only after preliminary sputum smear microscopy, which increases the economic benefits of screening by 19% and the effectiveness of activities, and prevents additional economic losses by 37% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%